Trail Running Eastern Massachusetts. - Kimball, Ben (University of Massachusetts Press, 2022)
"Eastern Massachusetts offers incredible trail-running opportunities, ranging from popular long-distance routes like the Bay Circuit Trail to lesser-known loops that run through the mountains and forests of the Quabbin watershed and Merrimack Valley region, and trails that pass alongside the shores of Cape Cod. All over the Bay State, there are trails suitable for runners of all levels waiting to be discovered and explored. Avid trail runner Ben Kimball offers a selection of fifty-one of eastern Massachusetts's most spectacular trail sites, including detailed trail descriptions, topographic maps, directions, parking information, safety tips, and much more. Both experienced and novice trail runners will find Trail Running Eastern Massachusetts to be an invaluable resource for exploring nature and getting a good workout, in the Boston area and beyond"--